096 Endovascular stenting for native coarctation of the aorta using the CP Numed covered stent. (22nd September 2015) - Hamid, T; Lazz-Onyenobi, G; Griffiths, L; Clarke, B; Mahadevan, S V
Abstract : Introduction: Primary endovascular stenting is now a recognised alternative treatment strategy to surgical treatment for native coarctation in adults. The availability of covered stents has made coarctation stenting more attractive, with less periprocedural complications and long-term follow-up. Objective: To assess early outcomes and blood pressure control in adults with a native aortic coarctation of the aorta undergoing primary endovascular stenting. DESIGN: - Primary data were collected prospectively from patients with native coarctation and systemic hypertension that underwent stenting of aortic coarctation using the CP Numed covered stent over 3 years period. Patients were assessed with 24 h ambulatory blood pressure monitoring (ABP) prior to the procedure (pre-stenting), at 6 weeks and 1 year following endovascular stenting. Results: There were 23 patients (14 male). Twenty-one patients had procedure under general anaesthesia. The procedure was technically successful in all patients. Mean age was 34±14 years. Peak aortic gradient across the coarctation fell from 26±12 mmHg to 7±5 mmHg (p<0.001) with stenting. Twelve patients were receiving anti-hypertensive medication prior to stenting with 11 receiving two or more agents. Blood pressure recordings are given in abstract 096 table 1 . Systolic blood pressure at 1 year dropped by 28 mmHg as compared to the pre-procedure (p<0.05). See abstract 096 table 1 . At 1-year follow-up eight patients remain on anti-hypertensive medication. One patient had successful re-dilatation of his stent 12 months later and there was no mortality. One patient had a false femoral aneurysm post-procedure needing repair. Conclusion: Significant improvements in the clinical and ABP blood pressure following stenting with the CP Numed covered stent are seen at 6 weeks sustained at 1 year. However there is a continued need for anti-hypertensive therapy and long term follow-up is required. (*As compared to the pre-stenting).